2017
DOI: 10.1097/aln.0000000000001518
|View full text |Cite
|
Sign up to set email alerts
|

Does a Platelet Transfusion Independently Affect Bleeding and Adverse Outcomes in Cardiac Surgery?

Abstract: Background Conflicting results have been reported concerning the effect of platelet transfusion on several outcomes. The aim of this study was to assess the independent effect of a single early intraoperative platelet transfusion on bleeding and adverse outcomes in cardiac surgery patients. Methods For this observational study, 23,860 cardiac surgery patients were analyzed. Patients who received one early (shortly after cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…69 Observational studies found an association between platelet transfusions and thrombotic complications in critically ill patients, 70,71 whereas no association was found in patients undergoing cardiac surgery. 72 Due to their design and inability to control for confounders, these studies cannot establish a causal relationship. Of note, the risk of coronary thrombosis could be higher if platelet transfusions are given in patients on antiplatelet therapy due to recent cardiac stenting.…”
Section: Thrombotic Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…69 Observational studies found an association between platelet transfusions and thrombotic complications in critically ill patients, 70,71 whereas no association was found in patients undergoing cardiac surgery. 72 Due to their design and inability to control for confounders, these studies cannot establish a causal relationship. Of note, the risk of coronary thrombosis could be higher if platelet transfusions are given in patients on antiplatelet therapy due to recent cardiac stenting.…”
Section: Thrombotic Complicationsmentioning
confidence: 99%
“…10 Van Hout evaluated 23,860 cardiac surgery patients and found that patients receiving platelet transfusion in the operating room experienced less blood loss but more often required vasoactive medication, prolonged ventilation, prolonged intensive care, and blood products postoperatively. 72 A therapeutic platelet transfusion approach is probably more appropriate than a prophylactic approach. Platelets may preferentially be transfused after separation from cardiopulmonary bypass after reversal of heparin, a time point when adequate hemostasis is required.…”
Section: Cardiac Surgerymentioning
confidence: 99%
“…12 As shown by Levy et al (2017), 13 there is still no consensus in the literature regarding triggers for platelet transfusion. Van Hout et al 14 reported that early platelet transfusions were associated with less postoperative blood loss but increased the risk for use of vasoactive drugs and extended mechanical ventilation, as well as prolonged stay in the intensive care unit (ICU). Several adverse events, including allergic reactions, infection and stroke, have been related to platelet transfusion.…”
mentioning
confidence: 99%
“…Perioperative platelet transfusion commonly is administered to patients after CPB based on the assumption that platelets are either damaged by CPB or lost in the surgical field. 12 Perhaps knowing more about platelet function would lead to a more rational use of platelet transfusion. However, in 1 retrospective propensity score-matched study, implementation of platelet function testing was shown to increase the use of desmopressin acetate without clear improvement in bleeding.…”
mentioning
confidence: 99%